Leadership and Career Development in Banking: Theories, Evidence, and a Strategic Framework for Talent Advancement - Priscilla Samuel Nwachukwu; Onyeka Kelvin Chima; Chinelo Harriet Okolo (International Journal of Scientific Research in Humanities and Social Sciences, 2024)
Leadership and career development have become pivotal components in shaping sustainable growth and competitiveness in the global banking sector. As banks navigate evolving regulatory pressures, technological disruption, and changing workforce expectations, the ability to cultivate effective leaders and advance career pathways for employees has emerged as a strategic imperative. This paper synthesizes theories of leadership including transformational, servant, and adaptive leadership and their relevance to banking institutions where decision-making, ethical responsibility, and innovation are critical. It also integrates human capital and career development theories, such as career stage models and protean career concepts, to illustrate how professional growth aligns with organizational objectives in banking. The evidence reviewed highlights that leadership quality strongly influences employee engagement, productivity, and customer trust, while career development opportunities drive talent retention and institutional resilience. Case studies across leading global banks demonstrate that structured mentoring programs, succession planning, and targeted leadership training contribute to improved financial performance and risk governance. Furthermore, empirical findings emphasize the role of inclusive leadership and diversity initiatives in broadening the talent pipeline and enhancing organizational adaptability in a rapidly digitizing financial environment. Building on these theoretical and empirical insights, the paper proposes a strategic framework for talent advancement in banking. This framework rests on three pillars: leadership development through structured learning, experiential exposure, and coaching; career growth pathways integrating performance management with skills development; and organizational alignment that ties individual aspirations to institutional goals, with strong emphasis on diversity, equity, and sustainability. By embedding these elements into core human resource practices, banks can cultivate future-ready leaders capable of balancing profitability with responsibility. Ultimately, the framework positions leadership and career development not only as internal workforce strategies but as drivers of institutional trust, competitiveness, and long-term stability in the banking industry.